Asbestos at the time of the First World War - Bianchi, Claudio; Bianchi, Tommaso (La Medicina del Lavoro, 2015)
Between the end of the 19th century and the beginning of the 20th numerous asbestos industries began operations in various parts of the world. At the time of the First World War there is ample evidence of the use of this mineral in shipbuilding, the aircraft industry and in the construction industry. In the years 1912-17 the writer Franz Kafka was co-proprietor of a small asbestos factory in Prague. Some of the writer’s novels and journal pages were inspired by this experience. In this way asbestos entered into the history of 20th century European literature. In 1917 asbestos extraction was started at the quarry in Balangero, near Turin, Italy. Risks related to the use of asbestos were known at the beginning of the 20th century and legislation aimed at preventing the harmful effects of the mineral were approved in Italy